Вклад профессора С. Кохмана в разработку проблематики польско-русских языковых контактов - Гарбуль, Людмила Павловна Павловна (Slavistica Vilnensis, 2011)
Liudmila Pavlovna Garbulj About the contribution of the professor S. Kochman into the working out of the problems on the Polish-Russian language contacts The article provides a short review of investigations of the Polish-Russian and Polish-East Slavonic language contacts in 15th –19th cc. of the noted Polish specialist in the philology of the Slavs professor S. Kochman, and his valuable contribution in the working out of these problems.